Cave macroinvertebrates used as bioindicators of water quality - Galindo Pérez, Ezel Jacome; Chávez Sandoval, Blanca Estela; Espinoza Graciano, Edson Mario; Villeda Callejas, María del Pilar; Flores Martínez, María del Carmen; Bhalli, Javed A.; Tejocote Pérez, Moisés; García Franco, Francisco (Tecnología y ciencias del agua, 2017)
Galindo-Pérez, E. J., Chávez-Sandoval, B. E., Espinoza- Graciano, E., Flores-Martínez, M. C., Villeda-Callejas, M. P., Bhalli, J. A., Tejocote-Pérez, M., & García-Franco, F. (September-October, 2017). Cave macroinvertebrates as bioindicators of water quality. Water Technology and Sciences (in Spanish), 8(5), 5-17.Caves are very fragile systems which are influenced by specific biogeographic and ecological patterns that maintain unique species of fauna, flora, and microbiota. One cave species, macroinvertebrates, represents a heterogeneous group of animal taxa which is in constant danger of extinction, principally due to anthropogenic activities. Macroinvertebrates have been widely used as bioindicators of the quality of biogeographic zones, ecosystems, and protected areas, as well as to determine protected species. The Boca del RÃo Cave is located in the biogeographic transition zone in Mexico's Neotropical region, and is home to a large enclave of different biotic elements. Twenty-nine organisms were collected and grouped into 19 families based on their morphological and physiological characteristics. The coefficient of taxonomic work (CTW) indicates that the taxonomic level family is the most consistent for all of the organisms collected. The Coenagronidae family was the most abundant in the study. The BMWP, ASPT, and SCI biotic index scores indicate that the water in the Boca del RÃo Cave is slightly contaminated, while the Family Biotic Index (FBI) indicates poor water quality with very substantial organic pollution. The diversity of macroinvertebrate families confirms that the Boca del RÃo Cave serves as an important refuge for fauna in the transition zone located in Mexico's Nearctic biogeographic region. This report represents the first study to use bioindicators to analyze the water quality of a cave system, and contributes to the inventories of macroinvertebrate cave fauna.Â